2022
DOI: 10.1039/d2ra05334a
|View full text |Cite
|
Sign up to set email alerts
|

A stable Fe/Co bimetallic modified biochar for ofloxacin removal from water: adsorption behavior and mechanisms

Abstract: Fe/Co bimetallic modified biochar (FMBC) was synthesized and characterized, and its adsorption mechanism of ofloxacin and the stability of FMBC were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…At pH < 5, electrostatic repulsion occurs between the positively charged surface of the composite and OFL + in solution, and at pH > 5, electrostatic repulsion also occurs between the negatively charged surface of the composite and the OFL – in solution. 19 , 38 In summary, electrostatic attraction is not the main adsorption mechanism of 70% BD-CaAl-LDH600 on ofloxacin, and the pH value of the solution is not a key factor affecting the adsorption performance of 70% BD-CaAl-LDH600 against ofloxacin. 39 …”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…At pH < 5, electrostatic repulsion occurs between the positively charged surface of the composite and OFL + in solution, and at pH > 5, electrostatic repulsion also occurs between the negatively charged surface of the composite and the OFL – in solution. 19 , 38 In summary, electrostatic attraction is not the main adsorption mechanism of 70% BD-CaAl-LDH600 on ofloxacin, and the pH value of the solution is not a key factor affecting the adsorption performance of 70% BD-CaAl-LDH600 against ofloxacin. 39 …”
Section: Resultsmentioning
confidence: 97%
“…In addition, the theoretical adsorption capacity ( Q e ) obtained by the pseudo-second order dynamic model was closer to the experimental adsorption capacity ( Q exp ). The results showed that the adsorption process of 70% BD-CaAl-LDH600 on ofloxacin conformed to the pseudo-second-order dynamic model, which was consistent with the kinetic behavior of adsorption reported by Hao et al…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations